1993
DOI: 10.1038/hdy.1993.118
|View full text |Cite
|
Sign up to set email alerts
|

Partial self-fertilization and inbreeding depression in two populations of Mimulus guttatus

Abstract: Inbreeding depression is likely to be a common selective force opposing the automatic selective advantage of self-fertilization in self-compatible plants and animals, yet relatively few studies have measured both the breeding system and inbreeding depression in natural populations. In this study, I estimated the frequency of selfing, using data obtained by gel electrophoresis, in two annual populations of the monkeyflower Mimulus guuatus for 2 years, and measured the relative performance of selfed and outcross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
148
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 69 publications
16
148
1
Order By: Relevance
“…However, Willis (1993a) observed little difference in inbreeding depression between greenhouse and field-grown M guttatus. Dole & Ritland (1993) have reported an 81 per cent reduction in fitness of self M guttatus progeny based on multigenerational changes in population inbreeding coefficients estimated from allozyme data.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, Willis (1993a) observed little difference in inbreeding depression between greenhouse and field-grown M guttatus. Dole & Ritland (1993) have reported an 81 per cent reduction in fitness of self M guttatus progeny based on multigenerational changes in population inbreeding coefficients estimated from allozyme data.…”
Section: Discussionmentioning
confidence: 90%
“…The 'elbow-room' hypothesis suggests that greater phenotypic variation among sibs could reduce competition and therefore increase mean progeny fitness (Young, 1981). This could lead to a selective advantage of mixed-mating systems because phenotypic variation may be maximized at intermediate levels of outcrossing (McCall et al, 1989 common phenomenon in M guttatus because of its mixed-mating system (Ritland & Ritland, 1989;Ritland, 1990;Dudash & Ritland, 1991;Willis, 1993a), but the data from our competition study and those presented by others (Schmitt & Ehrhardt, 1990;Argyres & Schmitt, 1992) do not support this application of the elbow-room hypothesis. We found that the difference in performance between self and outcross progeny was greatest when self and outcross progeny were grown together, although the differences among competitive regimes fell short of significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was consequently more opportunity for progeny from selfing and outcrossing to differ, and inbreeding depression was therefore higher in the greenhouse. Nevertheless, other studies conducted in both environments have found higher inbreeding depression in the field (Dudash 1990) or no difference (Willis 1993a). The variety of results further highlights the dependence of inbreeding depression on environmental conditions (Griffing and Langridge 1963;Griffing 1990).…”
Section: Inbreeding Depression At Different Life Stagesmentioning
confidence: 87%
“…If the interactions among loci are neither additive nor multiplicative (e.g. Sved & Wilton, 1989 ;Willis, 1993 ;Charlesworth, 1998), then a more complicated transformation may be required.…”
Section: (Iii) Inbreeding Depression Ersus Genetic Ariationmentioning
confidence: 99%